Selenium Status of School Children in IDD Endemic and Non Endemic Areas - . Rimbawa; Faisal Anwar; Eddy S Mudjajanto; Sri Adiningsih; Maya Sri Maryani (Media Gizi dan Keluarga, 2000)
The objectives of the study was to observe relationship between determinant parameters of iodine status and determinant parameter of selenium status among the elementary school children in determining IDD problem. The study was conducted in two villages of coastal area of Pasuruan, East Java Province using 24 samples in endemic area of IDD and 22 samples in non endemic area of IDD. Iodine status was measured based on urinary excretion of iodine (UEI) and thyroid hormones consentration (TSH, FT4, T3) while selenium status masured using selenium content of blood serum. The results of the study show that iodine status as measured by UEI and FT4 of samples living in endemic area (8,3% normal and 95,8% normal respectively) are statistically different from those in non endemic area (100% normal and 95,4% normal respectively) while iodine status as measured by TSH and T3 in endemic area (87,5% normal and 95,8% normal respectively) are not statistically different from those in non endemic area (100% normal and 100% normal respectively). The average selenium content in serum owned by samples in two areas are not statistically different. However if the data was classified based on normality categories, it is shown that samples in endemic area of IDD have lower category in selenium status (79,19%) compared to those in non endemic area of IDD (9,09%). There are significant correlation between T3 and FT4,, T3 and selenium content of serum, and between FT4 and selenium content of serum in non endemic area. The result of regression analyses of joined samples from endemic and non endemic areas showed that selenium content of serum and UEI were closely related to iodine and selenium intake (r=0,402 and r=0,510).Keywords: selenium, iodine status, school children